USING OUTLINING TECHNIQUE TO IMPROVE THE ABILITY OF THE STUDENTS OF THE ISLAMIC EDUCATION STUDY PROGRAM IN WRITING A RECOUNT TEXT - Amirudin Latif (Premise: Journal of English Education and Applied Linguistics, 2014)
This study was intended to improve the ability of the students of the Islamic Education Study Program in writing a recount text by outlining technique. They were guided to write a recount text based on the outline they made before producing the text. The teaching and learning activities consisted of leading the students to make an outline, assigning them to make an outline, leading them write a recount text based on the outline, and the last assigning them to write a recount text based on the outline. The result showed that the students’ ability in writing recount texts was improved. In the end of Cycle 2, there were 25 out 30 students who obtained score > 70. Hence, the outlining technique is very helpful to improve the students’ ability in writing recount texts.